Research on lake water level and its response to watershed climate change in Qinghai Lake from 1961 to 2019 - Li, Xiaodong; Zhang, Tingjun; Yang, Daqing; Wang, Guanxin; He, Zhuolun; Li, Lin (Frontiers in Environmental Science, 2023)
Lake water level reflects the dynamic balance of water input and output/loss and is a sensitive indicator of climate change and variation. Lake storage and regulation are also important for water resources assessment and local/regional socio-economic developments. The objective of this study was to investigate changes in Qinghai Lake water level/area and environmental factors during 1961–2019, using ground-based measurements and satellite remote sensing data. The results revealed two primary phases: during the first phrase (1961–2004), the lake water level lowered by 8 cm/year (P<0.01), while in the second phase (2004–2019), it rose markedly by 18 cm/year (P<0.01). The lake area increased in April and September between 1990 and 2019, but since 2004 the increases have been more significant. Air temperature near the lake during 1961–2019 warmed by 0.39°C/10 years and precipitation increased by 17 mm/10 years. Annual river runoff increased at 14.3 mm/10 years from 1961 to 2019, however, runoff decreased (−7 mm/10 years) during the first phase from 1961 to 2004 and increased significantly (85 mm/year) during the second phase from 2004 to 2019. The increases in precipitation and river runoff were the predominant factors contributing to lake water level rises and area expansion, while a decreasing lake water level and area reduction corresponded to reduced precipitation and river runoff and increased evaporation.